Feasibility of Transseptal Access in Patients With Previously Scarred or Repaired Interatrial Septum. (17th August 2015) - ARKLES, JEFFREY; ZADO, ERICA; SUPPLE, GREGORY; FRANKEL, DAVID S.; CALLANS, DAVID; MARCHLINSKI, FRANCIS; DIXIT, SANJAY
Challenging Transseptal Access Background Many patients (pts) with interatrial septal repair (ASR) and/or multiple prior transseptal puncture (MTSP) are being referred for atrial fibrillation (AF) ablation. We examine the feasibility of repeat TSP in these settings. Methods Records were reviewed from a single center from 2001 to 2012. Criteria for MTSP were >2 priorAF ablation procedures and criteria for ASR were prior surgical or percutaneous interatrial septal repair. Intracardiac echocardiography (ICE) was used for all procedures. Repeat transseptal puncture (TSP) outcomes were classified as (1) routine, (2) challenging (additional tools, sheaths, multiple attempts), (3) failed, or (4) complicated (adverse event possibly related to TSP). Five hundred pts selected at random over the same time period undergoing 1st AF ablation without history of prior cardiac surgery were used as control. Results Two hundred and fifty‐one pts met the criteria (MTSP = 224; ASR = 27). TSP was routinely accomplished in the majority (212 pts [95%] in MTSP; 20 pts [74%] in ASR). In the MTSP group, the number of challenging/failed cases increased proportionately with number of prior AF ablation procedures. There were no complications in the ASR group and 2 (1%) in MTSP. This was not different from that in the control arm (n = 6 [1%]; P = ns). Pericardial effusion was the only complication seen in all groups. Conclusions In the majority of pts with scarred and/or repaired IAS, repeat TSP can be routinely accomplished using ICE guidance without any other special tools. Although repeat TSP can be occasionally difficult in pts with MTSP and ASR, it can be accomplished in the majority without serious complications.